Urban Interiority: Emerging Cultural and Spatial Practices - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2021)
Discourses on the urban interior recently have emerged as a series of provocations and experimentations that highlight the critical understanding of the urban realm from the interiority perspective. In the fast-moving development of modern global cities, the urban interior concept becomes increasingly important. Cities are fast becoming containers for contemporary spatial practice, with urban spaces becoming melting pots of diverse cultures and communities. Viewing urban settings from the interiority perspective allows us to comprehend unique local characters in particular contexts. This issue of Interiority presents a collection of works that illustrate the expanded understanding of the urban interior, especially in relation to cultural and spatial practice in urban contexts. This issue presents multiple perspectives on understanding the urban interior, raising arguments on how its spatial condition could perform as a container of cultural practice, while simultaneously offering possibilities on manoeuvring within the urban interior context through various ways of reading, interpretation and intervention. These perspectives and approaches promise further possibilities to expand our interior architectural practice in responding not only to current contemporary practice, but also to the future of urban inhabitation.